The Old Testament speaks ; v. 1 God's Word for a former generation explained for today's people - Fleming, Donald C. (Kowloon, Hong Kong Living Books for All, 1980)
Contents : v.1 : Genesis, Exodus.
Brethren writer. Donated by the author.
Keywords: Bible. O.T. -- introductions